New Approaches for Regeneration of an Outstanding Baroque Living Heritage, the Széchenyi Linden Allée in Hungary - Kinga Szilágyi; Barnabás Tóth; Judit Doma-Tarcsányi; Anna Mohácsi; Krisztina Szabó (Land, 2024)
Allées used to be the essential artistic tools and indispensable parts of the strictly architectural, formal Baroque gardens. Beyond the practical purposes of edging paths and garden ways for walking, hunting, or horse and carriage riding, allées played a vital role in marking visual and landscape connections and thus the spatial projection of the noble estate, its wealth, and social rank. In Historical Hungary, Baroque architecture and garden art appeared in German-Austrian and French examples in the 18th century. The Széchenyi Linden Allée is an outstanding linear garden space of Baroque Garden art at Nagycenk, West Hungary. The generous composition, created by the prominent Count Széchenyi family in the mid-18th century, has remained a magnificent entity in the landscape ever since. Despite barely two hundred years of detected or unknown environmental or habitat changes, as early as 1942, the allée received a nature conservation nomination. More than a half-century later, in 2002, the allée became a historical and landscape aesthetical heritage within the Fertő-Hanság Cultural Landscape World Heritage site. Unfortunately, the once magnificent tree lines have severely eroded in recent decades due to mature trees’ subsequent death, inadequate replacement, lack of regular maintenance and tree care, and effects of climate change. In recent years (2011, 2018), landscape and horticultural analyses and visual and instrumental tree assessments were performed to help the conservation and rebirth of the allée, maintain the mature trees, and restore the landscape within a long-term renewal plan. Along with the 2018 survey and plan, the short-term maintenance works were completed in 2019–2020. This study, based on site surveys in 2022 and 2024, aims to identify the results of the primary management, analyses the vitality of mature trees after crown reductions, and then proposes a resilient and sustainable regeneration method with the habitat, cultural, natural, and genetic heritage, and the feasible maintenance contexts in focus. As proposed in the 2018 plan, the reproduction of mature trees started in 2020 and resulted in well-developing grafts for a later allée restoration. Due to the challenges of climate change, the regeneration project requires a special, long-term restoration management plan with a special focus on the still vital and possible remaining mature trees, the well-growing individuals from previous replanting, and the nursery school seedlings conserving the genetic heritage of the Széchenyi lime trees with long-viability capacity.